Inadvertent vertebral artery injury due to central venous line catheterization - W Mustapha, Wan Irfan; Ralib, Razali (IIUM Press, 2022)
A 66‐year‐old man with underlying DM, HPT and HPL presented with hypertensive urgency noted BP was 217/106 mmHg on arrival. Initial CT Brain was done showed multifocal multiages cerebral infarctions. Subsequent few CT Brains were done later due to the patient was deteriorated. In the ward, the patient developed choking episodes, and breathlessness led to aspiration pneumonia. In view of impending respiratory collapse, the primary team decided to intubate and inserted a quadruple central venous line (CVL) for multiple central drug infusions. Chest X-Ray (CXR) was done noted malposition of CVL supported with blood gases showed arterial in origin. CTA neck was done noted that the tip of the CVL was placed in the left subclavian artery. The patient was planned for left subclavian artery stenting. Digital subtraction angiography revealed the CVL is had punctured into the pre-foramina of the 7th cervical region of the left vertebral artery instead of from direct left subclavian artery puncture. Successful stenting of the left subclavian artery and followed by compression over the puncture site. However, the patient succumbed to death due to septic shock with multiorgan failure.